Alkitab Dan Kritik Alkitab - Zega, Fati Aro (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2021)
The Bible is the single most criticized and most freely criticized book, and no other Bible is so openly criticized. Even though the Bible never flinches. Although not all criticism is bad. The purpose of the author in this article is to understand how biblical criticism becomes the basis for exploring God's word. Using a qualitative descriptive text study with a literature literature approach, it can be concluded that there are two levels of research that are critical of the Bible, namely the level of Lower Criticism and Higher Criticism, even though all of them use philosophy and rasii in researching the Bible. This group at that time was known as the bearers of Liberal Theology. Through this article the author describes his research on nine models of criticism of the Bible which more discredit the sacredness and glory of the Bible rather than admit it.AbstrakAlkitab adalah satu-satunya buku yang paling banyak dikritik dan paling bebas dikritik, juga tidak ada Kitab Suci lain yang begitu terbuka dikritik. Sekalipun Alkitab tidak pernah bergeming. Walaupun memang tidak semua kritik itu buruk. Tujuan penulis dalam artikel ini supaya dapat memahami bagaimana kritik Alkitab menjadi dasar untuk menggali firman Allah. Menggunkan kajian teks deskritif kualitatif dengan pendekatan literature pustaka maka dapat disimpulkan bahwa ada dua level penelitian yang kritis terhadap Alkitab, yaitu level Lower Criticism dan Higher Criticism, walau semuanya sama-sama mengunakan filsafat dan rasii dalam meneliti Alkitab. Kelompok ini pada masanya dikenal sebagai pengusung Teologi Liberal. Melalui artikel ini penulis mendeskripsikan penelitian atas sembilan model kritik atas Alkitab yang lebih banyak mendeskreditkan kesakralan dan keagungan Alkitab daripada mengakuinya.